Illicit Narcotic Economies and State Fragmentation: Colombia and Afghanistan - Cheng, Huixin Shirley (2011)
This thesis argues that the illicit narcotics economy in Afghanistan and Colombia is the central force fragmenting state power through two main processes of internal regression and external attack. Internal regression refers to the capture, infiltration and corruption of the state by the drug industry that impairs effective state function. External attack refers to the territorial control, coercive force and political legitimacy that the illicit economy provides non-state armed actors. In this way, I contend that the fragmentation of state power by the illicit narcotics economy is two- fold. First, it diminishes state power in absolute terms - hindering the effective state function in terms of key institutions. Second the illicit narcotics reduces state power in relative terms - drug rents providing for the growth in reach and operational capacities of non-state power rivals when the state at the same time is losing its own